An efficient homogenization technique for fiber tows in textile composites with emphasis on directionally dependent nonlinear stress–strain behavior. (15th January 2019) - Choi, Heeyoung; Heinrich, Christian; Ji, Wooseok
Abstract: Now it is common to utilize a FE-based representative volume element (RVE) model to study the mechanical performances of textile composites. Complex architecture of fiber tows can be explicitly reflected in the RVE model, but a homogenization process for the tows, bundle of micrometer-scale fibers bound by a matrix material, is still required for the meso-scale model. We present a systematic yet simple approach to homogenize the fiber tow including directionally dependent nonlinear stress–strain responses. Nonlinear behavior of the matrix material is considered in the present homogenization method through the well defined Hill's anisotropic plasticity model. Parameters required for the anisotropic plasticity model are obtained from virtual test results at the fiber/matrix level. Tension and shear tests on plain weave textile composites are performed to validate the present numerical approach. It is also demonstrated that the homogenization technique can also be utilized to isolate the matrix stress–strain curve from composite shear stress-shear strain data.